EFFIGI: An Efficient Framework for Implementing Global Illumination. - LEESON, WILLIAM; COLLINS, STEVEN; O'SULLIVAN, CAROL ANN (My University, 2000)
This paper presents a rendering framework called EFFIGI (Efficient Framework For Implementing Global Illumination) that uses interfaces which express both geometric concepts and mathematical ones, using object-oriented and component objects mnethods. EFFIGI facilitates the development of new techniques and the implementation of existing ones, by providing a flexible but comprehensive geometric and mathematical architecture. The framework eliminates the need for users to implement an entire system, enabling them to focus only on those areas of partiucular interest.
PUBLISHED
Keywords: rendering framework; object-orientated design